Holiday under wraps - Mettner, Katie (Mettner, Katie. Secure One., 2024)
"He'll do anything to protect her but this Christmas there will be nowhere left to run... It takes everything former army officer Lucas Porter has to cope with PTSD--and his new life as a security technician. But he plunges back into danger to help the one woman he never forgot. Now he and former military specialist Delilah Hartman are only seconds ahead of trained killers as they battle a brutal Minnesota blizzard. And keeping her safe means Lucas must resist the reignited passion between them. But will exposing the truth give them a life together--or become an inescapable trap?" --